A parasztpolgárosodás "finn útja" : Kodolányi János finnországi tevékenysége és finn útirajzai - Váradi, Ildikó (2010)
In my thesis I focus on the work of János Kodolányi, who was one of the most significant authors of the twentieth century in Hungarian literature. My dissertation deals with a lesser known part of his works, namely his connections to Finland and Finnish culture, in addition to the observations made during his trips to Finland. Kodolányi was in Finland five times between the years 1936-38. He wrote many articles for several Hungarian newspapers about his experiences. His first travel book, Suomi, a csend országa (Suomi - The Country of Silence), based on these texts, was published in 1937. Two years later he released another book about his travels, called Suomi titka (Suomi's Secret). Additionally, these volumes were published together in the book entitled Suomi and strongly influenced and shaped Hungarians' image of Finland between the world wars. I research - on the ground of travelogues - the reasons, why Kodolányi travelled to Finland and his Finnish circle of friends, his intensive social life and literal action in Finland. I try to answer the following questions: how the Hungarian traveller saw and perceived Finland and Finnish society in his travel books, what kind of picture he received regarding the Finnish peasantry in the course of his travels? The image that Kodolányi had about Finland was influenced by his own cultural and historical tradition, or rather, by his own social environment, and the problematic socio-political conditions of Hungary between the two world wars. Kodolányi tried to solve the social, political and cultural problems of Hungary by his idealized image and the so called "Finnish model". Referring to tnis I show the connections between Kodolányi's publications, bool<s concerning Finland and work there with the Hungarian 'Populist Writers" who represented the so called theory of "Third Way" between Western democracy and Russian socialism. I analyse the image of Kodolányi and the connections between his travelouges and the so called "Third Way" by the perspective of cultural anthropology.